Analisa Keandalan Kolam Tandon Air Baku Dengan Inlet Dari Parit Yang Dipengaruhi Oleh Pasang Surut - Fuad, Asril; Siswanto, Siswanto; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Standard amount of water required progressively mount along growth of resident and industry. Exploiting of river as source of standard water require to utilize and fulfill standard amount of water required of society. Sei Salak reservoir pond one of the form exploiting of river as source of standard water. To evaluate ability of pool to fulfill society amount of water required needed a study to calculate pool reliability of Sei Salak reservoir pond. Source of Sei Salak reservoir pond come from year rainfall data 2000 up to year 2014 at station of inhil and of intake through salak river influenced by ebb. Stream debit inflow simulation pool with debit outflow with intake of water equal to 61 litre / second. The simulation results operational for 8 hours reservoir pool memilkik 100% reliability. The simulation results operational for 10 hours a reservoir pond memilkik reliability of 99.98%. The simulation results operational for 12 hours a reservoir pond memilkik reliability of 99.93%. Keywords: reliability, amount of water required, reservoir pond, pool simulation